Acute effects of whey protein isolate on blood pressure, vascular function and inflammatory markers in overweight postmenopausal women. - Pal, Sebely; Ellis, Vanessa (Cambridge University Press, 2011)
Previous evidence indicates that chronic consumption of dairy whey proteins has beneficial effects on CVD risk factors. The present study investigated the postprandial effects of whey protein isolate on blood pressure, vascular function and inflammatory markers in overweight and obese postmenopausal women. This was a randomised, three-way cross-over design study where twenty overweight and obese postmenopausal women consumed a breakfast meal in conjunction with one of three supplements: 45 g whey protein isolate, 45 g sodium caseinate or 45 g of a glucose control. Fasting and postprandial blood samples, blood pressure and pulse wave analysis readings were taken for up to 6 h. After consumption of the meal, both systolic and diastolic blood pressure, and augmentation index (AI) decreased initially for all interventions and gradually returned to baseline levels by 6 h. However, there were no significant differences in AI, systolic or diastolic blood pressure within or between the glucose control, casein or whey groups. There were also no significant group effects on plasma inflammatory markers (IL-6, TNF-a and C-reactive protein). The health effects previously seen with chronic whey protein ingestion were not seen in the acute 6 h postprandial period in relation to blood pressure, vascular function or inflammatory markers when compared with casein and a glucose control. This suggests that such effects are better observed from the long-term consumption of whey proteins.